1
$\begingroup$

The questions itself is in "improper integrals" subject.

$$\int \frac{2x}{x^{2}-1}$$

Here is an antiderivative: $\ln(x^{2}-1)|_{x=-1}^{x=1}$

If I just place numbers instead of $x$ I get $\ln(0)-\ln(0)$ which is like writing number-number=zero. The teacher however said that this was a mistake and that it is not based on same principle. why? is it not like substracting a number from itself?

$\endgroup$
  • 1
    $\begingroup$ don't forget $dx$ $\endgroup$ – J. W. Tanner Jul 19 at 14:01
  • $\begingroup$ Well, what is $ln(0)$? $\endgroup$ – Sudix Jul 19 at 14:27
7
$\begingroup$

It is true that $\ln(x^2-1)$ is an antiderivative of $\dfrac{2x}{x^2-1}$ on an interval where $\ln(x^2-1)$ is defined and differentiable. But unless you want to get into complex values for logarithms of negative numbers, you won't want to use this for $-1 < x < 1$. Instead, for $-1 < x < 1$ you could take the antiderivative as $\ln(1-x^2)$.

Then $$\int_a^b \dfrac{2x}{x^2-1} \; dx = \ln(1-b^2) - \ln(1-a^2)$$ for $-1 < a < b < 1$. But you can't use this for $a=-1$ and $b=1$, because $\ln(0)$ is undefined. In fact, you can't take the limit as $a \to -1$ and $b \to 1$, because $\ln(z) \to \infty$ as $z \to 0+$. Now you might say, why not take
$$ \lim_{b \to 1-}\int_{-b}^b \dfrac{2x}{1-x^2}\; dx = \lim_{b \to 0+} 0 = 0$$ The trouble is that if you do the limit differently, with $a \ne -b$, you'll get a different answer. For example, $$ \lim_{b \to 1-} \int_{-b^2}^b \dfrac{2x}{1-x^2}\; dx = \lim_{b \to 1-} \ln(1+b^2) = \ln 2 $$ So all we can say is $$ \int_{-1}^1 \dfrac{2x}{x^2-1}\; dx \ \text{diverges} $$

$\endgroup$
4
$\begingroup$

The map $x\mapsto\ln(x^2-1)$ is an antiderivative of $\dfrac{2x}{x^2-1}$. But if you replace $x$ by to concrete numbers and compute their difference, all you get as number, not an antiderivative of that function. Besides, $\ln(0)$ is undefined.

However, it is true that$$\lim_{t\to1^-}\int_{-t}^t\frac{2x}{x^2-1}\,\mathrm dx=0.$$That is so because, for each $t\in(0,1)$,$$\int_{-t}^t\frac{2x}{x^2-1}\,\mathrm dx=\ln(t^2-1)-\ln\bigl((-t)^2-1\bigr)=0.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.